Contact psychophysiological and neural functions with technical and tactical readiness volleyball - Glazyrin I. D.; Artemenko B. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Set the level of neural development, psycho-physiological functions in highly skilled volleyball players. Defined technical and tactical preparedness highly skilled volleyball players in the competitive period of the annual cycle of training. The study involved six masters of sport and 8 candidates for the master of sports. That the quality of play activities and the successful execution of technical elements depend on functional mobility, strength and reactivity of nerve processes, associative thinking, memory and attention. The results, which may have a prognostic value. It is shown that the neurodynamic functions are genetically determined. It is recommended to use them for the initial recruitment and selection stages for sports improvement. The necessity influence the types of thinking, memory and attention in the training process of volleyball players.